2016
DOI: 10.1039/c6sc00974c
|View full text |Cite
|
Sign up to set email alerts
|

Near diffusion-controlled reaction of a Zn(Cys)4 zinc finger with hypochlorous acid

Abstract: Reaction rate constants of HOCl with zinc-bound cysteines are determined, demonstrating that zinc fingers are potent targets for HOCl and may serve as HOCl sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…That same study showed cysteines bound to zinc are by far the most reactive protein residue with HOCl, achieving a near diffusion-limited rate of 9.3 × 10 8 M −1 s −1 , almost 3 orders of magnitude greater than cysteine alone (Lebrun et al, 2016), and in fact also exhibit decreased reactivity with hydrogen peroxide and oxygen (Bourlès et al, 2011). Previous work has identified numerous other proteins containing zinc-bound cysteines that are targets for HOCl oxidation including Hsp33 (Lebrun et al, 2016), and alcohol dehydrogenase, which is 3000-fold more reactive with HOCl than peroxide (Crow et al, 1995). The example we found to be most similar to TlpD is the activation of human neutrophil collagenase that occurs by HOCl oxidation of a single zinc-bound Cys, a mechanism coined as a “Cys-Zn switch” (Springman et al, 1990; Van Wart and Birkedal-Hansen, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That same study showed cysteines bound to zinc are by far the most reactive protein residue with HOCl, achieving a near diffusion-limited rate of 9.3 × 10 8 M −1 s −1 , almost 3 orders of magnitude greater than cysteine alone (Lebrun et al, 2016), and in fact also exhibit decreased reactivity with hydrogen peroxide and oxygen (Bourlès et al, 2011). Previous work has identified numerous other proteins containing zinc-bound cysteines that are targets for HOCl oxidation including Hsp33 (Lebrun et al, 2016), and alcohol dehydrogenase, which is 3000-fold more reactive with HOCl than peroxide (Crow et al, 1995). The example we found to be most similar to TlpD is the activation of human neutrophil collagenase that occurs by HOCl oxidation of a single zinc-bound Cys, a mechanism coined as a “Cys-Zn switch” (Springman et al, 1990; Van Wart and Birkedal-Hansen, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Such specificity can be understood based on differences between the reactivity of these species with protein residues. H 2 O 2 in the micromolar range almost exclusively reacts with cysteine, and to a lesser extent with methionine, whereas the targets of HOCl are more broad and exhibit extremely fast reaction rates; a detailed kinetic analysis measured the reaction rate of HOCl with Cys to be 3.0 × 10 7 M −1 s −1 , and 3.8 × 10 7 M −1 s −1 for Met (Lebrun et al, 2016). That same study showed cysteines bound to zinc are by far the most reactive protein residue with HOCl, achieving a near diffusion-limited rate of 9.3 × 10 8 M −1 s −1 , almost 3 orders of magnitude greater than cysteine alone (Lebrun et al, 2016), and in fact also exhibit decreased reactivity with hydrogen peroxide and oxygen (Bourlès et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins that contain the [Zn(Cys) x (His) y ] architecture (where x+y=4) are implicated in HOCl sensing through a reversible oxidation process at the zinc‐bound cysteine(s), launching redox signaling cascades that can regulate protein activity, [4] mitigate protein aggregation, [5] increase bacterial resistance, [6] and alter bacterial localization [7] . While the reactivity of zinc‐bound thiolates to oxidants such as H 2 O 2 is well documented via experimental [8,9] and theoretical studies, [10,11] comparable work with HOCl is still in its infancy [12] . Furthermore, apart from modulating the protonation state [13] and nucleophilicity [14] of the bound thiolate at physiological pH, no additional role of Zn 2+ complexes in governing the reactivity of the bound thiolates toward oxidants has been explored.…”
Section: Figurementioning
confidence: 99%
“…This results in localized unraveling in the helix containing the zinc‐binding cysteine to reversibly inactivate the chemoreceptor and promote a bacterial swimming response to facilitate chemoattraction. These CZB domains present a unique opportunity to study zinc‐thiolate reactivity with HOCl, as high‐resolution experimental structures offer a pristine view of the zinc‐binding core, and they contain a single reactive cysteine, as opposed to other systems, such as zinc‐finger proteins, [12] that contain multiple cysteines and undergo complicated disulfide shuffling. Furthermore, CZB domains are present in numerous bacteria, including many enteric pathogens, and so understanding their molecular function has relevance for human diseases [15] .…”
Section: Figurementioning
confidence: 99%